Clinico-epidemiological Profile of Onychomycosis Attending in a Tertiary Care Hospital - Khondker, L; Choudhury, AM; Shah, MOR; Shahidullah, M; Khan, MSI; Ahamed, ARS (Journal of Bangladesh College of Physicians and Surgeons, 2012)
A cross sectional study, conducted in the department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU) for duration of January 2009 to December 2010. Hundred twenty patients with onychomycosis were selected by purposive type of nonprobability sampling technique. Majority of the patients 61(150.8%) were in the age group of 21-30 years old. Mean age of the patients were 32.8±14 years and most of the patients were house wives 36(30.0%). Disfigurement 117(97.5%) and discomfort 89(74.2%) were more common chief complaints of the patients. The mean duration of disease was 20.4±15.4 months and nail fold changes were associated with 37(30.8%) patients and more than a half 63(52.5%) of the patients had history of wet works. Regarding the history of past illness, it was observed that previous onychmycosis found 26(21.7%), nail trauma 26(21.7%) and immune suppression 6(5.0%). In endocrinopathies, hypothyroidism was observed in 1(0.8%), Diabetes Mellitus 6(5.0%) etc. Regarding the pattern of nail changes, thickening of nail plate 88(73.3%), onycholysis 67(55.8%), subungunal hyperkeratosis 61(50.8%) were more common changes. Paronychia was observed in 34 (28.3%) cases. In concomitant fungal infection, it was observed that T. manuum in 6(5.0%), T. pedis 3(2.5%), Interdigital intertrigo 2(1.7%) and T. cruris 1(0.8%). This was a study on a limited number of cases. Future studies must include economical support, then large sample size could be ensured and study finding would be more reliable. There is a great need of epidemiological studies also, with sufficient follow-up, systematic reviews and meta-analyses on this issue. DOI: http://dx.doi.org/10.3329/jbcps.v30i2.11408 J Bangladesh Coll Phys Surg 2012; 30: 78-84